Microstructure and mechanical properties of calcium phosphate cement/gelatine composite scaffold with oriented pore structure for bone tissue engineering - Qi, Xiaopeng; He, Fupo; Ye, Jiandong (Journal of Wuhan University of Technology. Materials science edition, 2012)
The macroporous calcium phosphate(CPC) cement with oriented pore structure was prepared by freeze casting. SEM observation showed that the macropores in the porous calcium phosphate cement were interconnected aligned along the ice growth direction. The porosity of the as-prepared porous CPC was measured to be 87.6% by Archimede’s principle. XRD patterns of specimens showed that poorly crystallized hydroxyapatite was the main phase present in the hydrated porous calcium phosphate cement. To improve the mechanical properties of the CPC scaffold, the 15% gelatine solution was infiltrated into the pores under vacuum and then the samples were freeze dried to form the CPC/gelatine composite scaffolds. After reinforced with gelatine, the compressive strength of CPC/gelatine composite increased to 5.12 MPa, around fifty times greater than that of the unreinforced macroporous CPC scaffold, which was only 0.1 MPa. And the toughness of the scaffold has been greatly improved via the gelatine reinforcement with a much greater fracture strain. SEM examination of the specimens indicated good bonding between the cement and gelatine. Participating the external load by the deformable gelatine, patching the defects of the CPC pores wall, and crack deflection were supposed to be the reinforcement mechanisms. In conclusion, the calcium phosphate cement/gelatine composite with oriented pore structure prepared in this work might be a potential scaffold for bone tissue engineering.